The process of differentiation between the Senatorial and the Equestrian Orders at the end of the Roman Republic - Souza, Alice Maria de (Romanitas - Revista de Estudos Grecolatinos, 2014)
The identity boundaries between the Equestrian Order and the Senatorial Order, since the inception of the both orders, were tenuous. However, at the end of the second century BC these two orders began to outline their limits more clearly, mainly due to a law proposed by Gaius Gracchus during his magistracy as tribune of the plebs. This is the object of this article, which aims to give an overview of the differentiation process between these two orders.